Simultaneous removal of nitrogen and arsenite by heterotrophic nitrification and aerobic denitrification bacterium Hydrogenophaga sp. H7 - Fan, Xia; Nie, Li; Chen, Zhengjun; Zheng, Yongliang; Wang, Gejiao; Shi, Kaixiang (Frontiers in Microbiology, 2023)
Nitrogen and arsenic contaminants often coexist in groundwater, and microbes show the potential for simultaneous removal of nitrogen and arsenic. Here, we reported that Hydrogenophaga sp. H7 was heterotrophic nitrification and aerobic denitrification (HNAD) and arsenite [As(III)] oxidation bacterium. Strain H7 presented efficient capacities for simultaneous NH4+-N, NO3--N, or NO2--N removal with As(III) oxidation during aerobic cultivation. Strikingly, the bacterial ability to remove nitrogen and oxidize As(III) has remained high across a wide range of temperatures, pH values, and shaking speeds, exceeding that of the most commonly reported HNAD bacteria. Additionally, the previous HNAD strains exhibited a high denitrification efficiency, but a suboptimal concentration of nitrogen remained in the wastewater. Here, strain H7 combined with FeCl3 efficiently removed 96.14% of NH4+-N, 99.08% of NO3--N, and 94.68% of total nitrogen (TN), and it oxidized 100% of As(III), even at a low nitrogen concentration (35 mg/L). The residues in the wastewater still met the Surface Water Environmental Quality Standard of China after five continuous wastewater treatment cycles. Furthermore, genome and proteomic analyses led us to propose that the shortcut nitrification-denitrification pathway and As(III) oxidase AioBA are the key pathways that participate in simultaneous nitrogen removal and As(III) oxidation.